2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

The Southern Ocean ecosystem under multiple climate change stresses ‐ an integrated circumpolar assessment - Julian Gutt; Nancy Bertler; Thomas J. Bracegirdle; Alexander Buschmann; Josefino Comiso; Graham Hosie; Enrique Isla; Irene R. Schloss; Craig R. Smith; Jean Tournadre; José C. Xavier (Global Change Biology, 2015)
A quantitative assessment of observed and projected environmental changes in the Southern Ocean ( SO ) with a potential impact on the marine ecosystem shows: (i) large proportions of the SO are and will be affected by one or more climate change processes; areas projected to be affected in the future are larger than areas that are already under environmental stress, (ii) areas affected by changes in sea‐ice in the past and likely in the future are much larger than areas affected by ocean warming. The smallest areas ( SO ) are affected by glacier retreat and warming in the deeper euphotic layer. In the future, decrease in the sea‐ice is expected to be widespread. Changes in iceberg impact resulting from further collapse of ice‐shelves can potentially affect large parts of shelf and ephemerally in the off‐shore regions. However, aragonite undersaturation (acidification) might become one of the biggest problems for the Antarctic marine ecosystem by affecting almost the entire SO . Direct and indirect impacts of various environmental changes to the three major habitats, sea‐ice, pelagic and benthos and their biota are complex. The areas affected by environmental stressors range from 33% of the SO for a single stressor, 11% for two and 2% for three, to SO ecosystem.